2016
DOI: 10.1002/rcr2.155
|View full text |Cite
|
Sign up to set email alerts
|

Cystic teratoma mimicking recurrent pleural effusion, complicated by Mycobacterium abscessus infection

Abstract: Teratomas of anterior mediastinum are rare. They are often slow growing, asymptomatic, and detected incidentally on chest imaging. Mycobacterium abscessus (M. abscessus) is an acid‐fast bacillus that is classified as a pathogenic “rapid growing” non‐tuberculous mycobacteria. It is an uncommon cause of human pathology, which may cause skin and soft tissue infection after skin injury following inoculation, minor trauma, and surgery. Here, we present an unusual case of benign cystic teratoma mimicking recurrent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…We found that mature teratoma with pleural effusion presented a high proportion in female patients during their young adult life. However, the literature search demonstrates the occurrence of mature teratoma with pleural effusion in patients as young as at 25 weeks of gestation and as old as 51 years 2,9‐61 . Respiratory symptoms are predominant and not specific which has led often to a delay in the diagnosis for as long as 2 years 2,9‐11,19,20,22,28,30,32‐60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that mature teratoma with pleural effusion presented a high proportion in female patients during their young adult life. However, the literature search demonstrates the occurrence of mature teratoma with pleural effusion in patients as young as at 25 weeks of gestation and as old as 51 years 2,9‐61 . Respiratory symptoms are predominant and not specific which has led often to a delay in the diagnosis for as long as 2 years 2,9‐11,19,20,22,28,30,32‐60 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature search demonstrates the occurrence of mature teratoma with pleural effusion in patients as young as at 25 weeks of gestation and as old as 51 years 2,9‐61 . Respiratory symptoms are predominant and not specific which has led often to a delay in the diagnosis for as long as 2 years 2,9‐11,19,20,22,28,30,32‐60 . The majority of studies were reported in high‐income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Mature teratoma is one of the least common anterior mediastinal tumors which grow slowly and it is asymptomatic in most cases [1] , [2] , [3] . Nonetheless, the most common clinical symptoms of mediastinal germ cell tumors include dyspnea (25%), thoracic pain (23%), cough (17%), fever (13%), weight loss (11%), superior vena cava occlusion (6%) and extrathoracic pain (5%) [4] while pleural effusion is rarely seen in such cases [5] .…”
Section: Discussionmentioning
confidence: 99%
“…These tumors grow slowly and they don't often have any symptoms so that they are rarely specified in CXR. Chest pain, dyspnea and cough are the most common symptoms of these tumors occurring because of the pressure effects on adjacent organs [1] , [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%